We never expected that a comparative study of failures in national and business intelligence - Barnea, Avner (Lexington Books, 2021)
"The basic premise of this book is that in both fields, national and business, intelligence gathered about adversaries or competitors regarding changes in the external environment support the decision-making process. In both fields the subject has been studied within its own framework without comparative analysis or mutual learning"--